Impact of Leaders Despotism on Subordinates Outcomes with Mediation of Psychological Contract Breach - KAYANI, MUHAMMAD BILAL; ALASAN, IMRAN IBRAHIM (The journal of contemporary issues in business and government, 2021)
The current study adds on to the existing literature by investing the outcomes of despotic leadership. Specifically, we investigate counterproductive work behavior could be a response to despotic supervision by employees’ working under them. Moreover, we investigate whether the proactive personalities are better at coping with despotic supervision at workplace. We measured the constructs under investigation from the nurses working in the public hospitals of Pakistan with a total sample of 386 nurses. Quantitative research was conducted by adopting quota sampling (provinces) and convenient sampling respectively. The results support the mediating effect between psychological breach of contract between despotic leadership and counterproductive work behavior. The moderating effect of proactive personality was however found to be insignificant. For individuals, proactive personality traits serve as an improvement of individual personalities to cope with despotic leaders at the job place; for organizations, our study results provide managers with specific despotic traits that may provoke breach of psychological contract and result into counterproductive work behavior. The current study adds on to the literature of despotic leadership specially in relation to workplace outcomes like counterproductive work behavior and psychological breach of contract. Further, the role of proactive personalities is enhanced and elaborated in coping with despotic leaders adding.